mobilePDR a mobile medical information system featuring update via Internet. - Bojovic, M. (IEEE Transactions on information technology in biomedicine)
This paper presents an analysis of usability of mobile prescription reference systems in medical practice, and presents implementation of mobilePDR (Physician's Desk Reference). Various aspects of mobilePDR are discussed: main functions, information content, performance and design issues, independent evaluation with other similar tools, and lessons learned from the system development.